Preventing hamstring injuries - Part 1: Is there really an eccentric action of the hamstrings in high speed running and does it matter? - Shield, A.; Murphy, S. (Sport Performance & Science Reports, 2018)
Hamstring injuries remain a major burden in sport (1) despite enormous research e orts and the development of apparently e ective prevention (2,3) and rehabilitation practices.(4) Interventions that work in amateur and lower levels of professional sport may not be fully implemented in the more crowded training and playing schedules of elite sport (5) and perhaps they work only in less t athletes or their bene ts are `drowned out' by other training methods? We suggest that belief systems and philosophies shared widely by expert coaches also reduce adoption of some evidence-based practices. van Hooren and Bosch recently argued that isometric conditioning may be more e ective at reducing hamstring injuries and more readily programmed into busy competition schedules than eccentric exercise.(6, 7) Here, we critique these arguments and o er some insights into an eccentric strength and sprint-oriented injury prevention program that has been employed to good e ect in the English Premier League. We do not claim that anecdotal evidence is in any way de nitive. Nor do we claim that isometric training doesn't work or that eccentric hamstring conditioning is the only e ective means of prevention. Instead we argue that recommendations to employ an isometric approach instead of an eccentric one are premature.